2014
DOI: 10.1103/physrevc.89.055210
|View full text |Cite
|
Sign up to set email alerts
|

Polyakov linear SU(3)σmodel: Features of higher-order moments in a dense and thermal hadronic medium

Abstract: In order to characterize the higher order moments of the particle multiplicity, we implement the linear-sigma model with Polyakov-loop correction. We first studied the critical phenomena and estimated some thermodynamic quantities. Then, we compared all these results with the first-principle lattice QCD calculations. Then, the extensive study of non-normalized four moments is followed by investigating their thermal and density dependences. We repeat this for moments normalized to temperature and chemical poten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
117
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(128 citation statements)
references
References 73 publications
10
117
1
Order By: Relevance
“…Various expressions fulfilling QCD symmetries in pure-gauge theory have been proposed [4,5,7,58]. In all our previous works [35,37,60,61], we have utilized the simplest polynomial-form. But, in the present work,…”
Section: A Short Reminder To Su(3) Polyakov Linear-sigma Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Various expressions fulfilling QCD symmetries in pure-gauge theory have been proposed [4,5,7,58]. In all our previous works [35,37,60,61], we have utilized the simplest polynomial-form. But, in the present work,…”
Section: A Short Reminder To Su(3) Polyakov Linear-sigma Modelmentioning
confidence: 99%
“…In finite magnetic field, the chiral phase-structure of (pseudo)-scalar and (axial)-vector meson masses has been analysed [31]. Recently, study of QGP in presence of external magnetic field has been conducted [31,36,37]. Furthermore, at nonzero magnetic field, viscous properties from Boltzmann-Uehling-Uhlenbeck (BUU) equation have been compare with the ones from Green-Kubo (GK) correlations in relaxation time approximation (RTA), which are based on relativistic kinetic theory [36].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the experimental and theoretical studies of charm physics turns to be a very active field in hadronic physics [1]. It was shown that the PLSM model, which is a QCDlike model, describes very successfully the phenomenology of the SU(3) quark-hadron structure in thermal and dense medium and also at finite magnetic field [2][3][4][5][6][7][8][9][10]. At low densities or as the temperature decreases, the quark gluon plasma (QGP), where the degrees of freedom of quark flavors, N f , are dominated, is conjectured to confine forming hadrons.…”
Section: Introductionmentioning
confidence: 99%
“…At vanishing quark masses, the chiral symmetries represent basic properties of the QCD Lagrangian, while at finite current quark masses, the chiral symmetry is explicitly broken [3] and the QCD phasediagram can be described by the first-principle LQCD [4,5] and various QCD-like approaches. In charactering SU (2) and SU(3), the Polyakov Nambu-Jona Lasinio (PNJL) model [6,7,8] and the Polyakov linear-sigma model (PLSM) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23] have been implemented. The SU(4) Lagrangian has the same structure as that of SU(3) [9], for instance.…”
Section: Introductionmentioning
confidence: 99%